2015
DOI: 10.4269/ajtmh.14-0838
|View full text |Cite
|
Sign up to set email alerts
|

Nodding Syndrome, Western Uganda, 1994

Abstract: Abstract. Nodding syndrome (NS) is a poorly understood condition, which was delineated in 2008 as a new epilepsy syndrome. So far, confirmed cases of NS have been observed in three circumscribed African areas: southern Tanzania, southern Sudan, and northern Uganda. Case-control studies have provided evidence of an association between NS and infection with Onchocerca volvulus, but the causation of NS is still not fully clarified. We report a case of a 15-year old boy with head nodding seizures and other charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…This revealed a number of patients with a particular form of seizures characterized by slow dorsoventral head movements, called head nodding or "nateera omutwe" in the local Rutooro language. 4,5 It was recognized that the head nodding seizures encountered in the study area of Kabende parish were very similar in their appearance with those in a report from an isolated area of the Mahenge mountains in Tanzania of the early 1960s, 4,6 but the significance of this observation was not immediately clear.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…This revealed a number of patients with a particular form of seizures characterized by slow dorsoventral head movements, called head nodding or "nateera omutwe" in the local Rutooro language. 4,5 It was recognized that the head nodding seizures encountered in the study area of Kabende parish were very similar in their appearance with those in a report from an isolated area of the Mahenge mountains in Tanzania of the early 1960s, 4,6 but the significance of this observation was not immediately clear.…”
Section: Introductionsupporting
confidence: 54%
“…13 A widely accepted definition of NS was drawn up in an international conference in Kampala, Uganda, 2012. 14 Recently, we have published a detailed case report, 5 indicating that the mentioned patients seen with head nodding in Kabende parish in 1994 4 were actually affected by NS. With the present article, we extend our analysis to the complete series of all patients identified in the study area between 1994 and 1996.…”
Section: Introductionmentioning
confidence: 99%
“…In retrospect, NS was also found in western Uganda (7,8) and suspected cases were reported from Liberia (9) and Cameroon (10). In many NS patients, initial head seizure are followed by other seizures types, progressing physical and cognitive deterioration, and death (6,8). To date, the exact causation of NS is not clarified, but epidemiological and case-control studies have shown a consistent correlation between NS and infection with Onchocerca volvulus (O. volvulus), a parasite known as the cause of river blindness in large parts of tropical Africa (2,4,11,12).…”
mentioning
confidence: 91%
“…Growing numbers of patients with NS were documented since the early 2000s in three distinct areas in the southern Sudan (3,4), southern Tanzania (1) and northern Uganda (5,6). In retrospect, NS was also found in western Uganda (7,8) and suspected cases were reported from Liberia (9) and Cameroon (10). In many NS patients, initial head seizure are followed by other seizures types, progressing physical and cognitive deterioration, and death (6,8).…”
mentioning
confidence: 99%
“…5 A 1994 case report demonstrated some initial efficacy for phenobarbitone, but long-term control was not achieved. 10 A 2013 case series in which four patients were treated with anti-epileptics provided mixed or no evidence for the efficacy of carbamazepine and phenobarbitone respectively. 41 In 2014 Winkler and colleagues demonstrated cessation or reduction of head nodding frequency in the majority of patients treated with anti-epileptic drugs.…”
Section: Autoimmunitymentioning
confidence: 99%